Vertically-heterostructured TiO2-Ag-rGO ternary nanocomposite constructed with {001} facetted TiO2 nanosheets for enhanced Pt-free hydrogen production. (18th January 2018) - Wang, Zhouyou; Low, Ze-Xian; Zeng, Xiangkang; Su, Bin; Yin, Yichun; Sun, Chenghua; Williams, Tim; Wang, Huanting; Zhang, Xiwang
Abstract: TiO2 nanosheets with high ratio of {001} facets were coupled with reduced graphene oxide (rGO) nanosheets through the link of silver (Ag) nanoparticles, forming a novel ternary nanocomposite photocatalyst with a vertical heterostructure, TiO2 -Ag-rGO. The vertical anchoring of TiO2 -Ag nanosheets between rGO sheets was confirmed by transmission electron microscopy (TEM), Raman spectroscopy, energy dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). Due to excellent separation of electron-hole pairs in the TiO2 nanosheets, enhanced electron transfer to rGO via Ag nanoparticles, the TiO2 -Ag-rGO nanocomposite exhibited an outstanding performance in photocatalytic hydrogen production, with a hydrogen production rate of 593.56 μmol g −1  h −1 . This study provides new insights to the development of Pt-free photocatalysts for hydrogen production. Highlights: A new vertically-heterostructured containing TiO2 - Ag-rGO was designed. The new "metal-link" concept was confirmed by experimental validation. Ag nanoparticles enhance the transfer of photo-excited electrons. Ag nanoparticles harvest more photons in vertically-heterostructured TiO2 -Ag-rGO. A three-fold improvement in hydrogen production was achieved by TiO2 -Ag-rGO.